Cognitive and Behavioral Contributions to Depression Severity, Quality of Life, and Functioning Among People Living With HIV in South Africa. Issue 1 (January 2023) - Andersen, Lena S.; Stanton, Amelia M.; Magidson, Jessica F.; Joska, John A.; O'Cleirigh, Conall; Lee, Jasper S.; Kagee, Ashraf; Witten, Jade A.; Safren, Steven A.
Highlights: Impact of rumination and behavioral activation on depression in HIV is unknown. This is particularly the case in resource-limited global settings like South Africa. Models showed higher levels of rumination significantly associated with depression. Behavioral activation (BA) is an important treatment target for this population. Models showed lower levels of BA significantly associated with depression. Only BA significantly associated with quality of life and functional impairment. Abstract: Cognitive-behavioral treatments for depression typically address both behavioral (e.g., activation) and cognitive (e.g., rumination) components, and consequently improve quality of life (QOL) and function in high-resource settings. However, little is known about the cross-cultural applicability and relative contribution of these components to depression symptom severity, QOL, and functional impairment in South Africa and other resource-limited global settings with high HIV prevalence rates. Persons with HIV ( N  = 274) from a peri-urban community outside Cape Town, South Africa, were administered multiple measures of depression (Hamilton Depression Scale, Centre for Epidemiological Studies Depression Scale, South African Depression Scale), cognitive and behavioral components related to depression (Ruminative Response Scale, Behavioral Activation for Depression Scale), and measures of QOL and functioning (Sheehan Disability Scale, Quality of Life Enjoyment and Satisfaction Scale—Short Form). Multiple linear regression models were fit to assess the relative contribution of behavioral and cognitive components to depression severity, QOL, and functional impairment in this population. Models accounting for age and sex revealed that lower levels of behavioral activation (BA) were significantly associated with all measures of depression, as well as with QOL and functional impairment (all p s < .01). Rumination was associated with all measures of depression (all p s < .01), but not with QOL or functional impairment. The consistent and unique association of BA with depression, QOL, and functional impairment bolsters its importance as a treatment target for this population.